Тривожна маскулінність фланера: компаративний аналіз романів «Туман» М. де Унамуно і «Записки Кирпатого Мефістофеля» В. Винниченка - Тищенко, А. (Слово і Час, 2021)
У статті здійснено порівняльний аналіз романів М. де Унамуно «Туман» та В. Винниченка «Записки Кирпатого Мефістофеля». Предмет розвідки — феномен тривожної маскулінності, котрий з’являється
в урбаністичному просторі і слугує симптоматикою руйнації патріархальної культурної парадигми. Головні герої романів поєднані спільними
проблемами ідентичності, сексуальності, гендерних ролей, які вони намагаються вирішувати у практиках ходіння вулицями міста. Водночас
обидва письменники втілюють у протагоністах різні підходи до осмислення кризи чоловічої ідентичності. Результати дослідження увиразнюють форми оприявнення фланерського дискурсу, що активно розвивався в
європейській літературі на початку ХХ століття. At the beginning of the 20th century, modernist literature starts to face the new existential
issues unfolded in the urban environment. One of these issues is the phenomenon of anxious
masculinity caused by the destruction of the patriarchal paradigm.
In the literatures that were moving from the traditional type of culture to urban and
modern, the writers described men who went out on the streets, converting themselves into
the urban cultural type known as flâneur. The practice of flânerie, first presented in French
literature, became popular in other European literatures as well, Spanish and Ukrainian not
being exceptions. However, the type of flâneur in these two literatures still requires a scrupulous
study.
The paper provides a comparative analysis of M. de Unamuno’s “Niebla” (“Mist”)
and V. Vynnychenko’s “Zapysky kyrpatoho Mefistofelia” (“Notes of Snub-Nosed
Mephistopheles”) aiming to analyze the represented types of flâneurs. The novels
demonstrate the specifics of flâneur’s discourse in Spanish and Ukrainian literatures, which
were undergoing modernization processes. The comparison of such elements as writers’
urban experiences, protagonists’ interaction with the urban space, meeting with the modern
women on the streets as the main plot element, and gender issues allowed defining different
reflections on anxious masculinity and broadening European flânerie discourse. In addition,
the analysis defined the protagonists of the novels as proto-flâneurs, which creates the
perspective for further studies of the flânerie in Spanish and Ukrainian literatures.
The results of the research provide arguments for the hypothesis that the flânerie is one
of the modernist perception strategies, symptomatic for European culture.